2017
DOI: 10.1002/mrd.22844
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress in pregnant sows: Thermal responses and subsequent performance of sows and their offspring

Abstract: Seasonal infertility is a significant problem in the swine industry, and may be influenced by photoperiod and heat stress. Heat stress during gestation in particular affects pregnancy, resulting in long-term developmental damage to the offspring. This review summarizes what is known about how heat stress on the pregnant sow affects lactation and her offspring. Sows responded to heat stress during gestation with increased rectal temperature, respiration rate, and skin temperature, and tended to reduce their act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 50 publications
5
40
1
5
Order By: Relevance
“…In agreement with previous studies, our data demonstrated a significant reduction in porcine PRL levels due to elevated ambient temperature. In our study, no significant effects of HS were observed on the number of live piglets born per litter, nor on litter birth weight; similar findings were reported by Lucy and Safranski (2017), who demonstrated no clear influences of gestational HS on the number of piglets born live per litter. The seasonal influences of our study and that have been reported previously on piglet traits at birth are mainly caused by a delayed response to ambient temperature, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous studies, our data demonstrated a significant reduction in porcine PRL levels due to elevated ambient temperature. In our study, no significant effects of HS were observed on the number of live piglets born per litter, nor on litter birth weight; similar findings were reported by Lucy and Safranski (2017), who demonstrated no clear influences of gestational HS on the number of piglets born live per litter. The seasonal influences of our study and that have been reported previously on piglet traits at birth are mainly caused by a delayed response to ambient temperature, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…These temperatures were within the range generally expected to induce HS in gestating and lactating sows since the average rectal temperature of sows in this study were 38.9 and 39.4 °C in gestation and lactation periods, respectively. The rectal temperature of sows in the present study was higher than the temperature reported in the meta-analysis by Lucy and Safranski (2017), in which thermoneutral (below 25 °C) and heat-stressed (25 to 35 °C) sows differed in rectal temperature by approximately 0.3 °C (38.15 and 38.47 °C for thermoneutral and heat-stressed sows, respectively) during the last two weeks of gestation. Furthermore, the lactating sows kept in high ambient temperature (above 25 °C) showed a 0.5 °C increase in rectal temperature, from 38.7 °C in comfort zone to 39.2 °C during HS (Ribeiro et al, 2018).…”
Section: Discussioncontrasting
confidence: 86%
“…Furthermore, the lactating sows kept in high ambient temperature (above 25 °C) showed a 0.5 °C increase in rectal temperature, from 38.7 °C in comfort zone to 39.2 °C during HS (Ribeiro et al, 2018). Several studies have shown that rectal temperature can be considered as an indicator of the thermoregulation process (Renaudeau and Noblet, 2001;Williams et al, 2013;Lucy and Safranski, 2017). Ribeiro et al (2018) reviewed 20 recent studies and reported that the thermal comfort zone for lactating sows (ranging from 15 to 25 °C) decreased voluntary feed intake and milk output significantly for each Celsius degree increase in ambient temperature above the thermal comfort temperature.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptive mechanisms include behavioral and metabolic adaptations. Pigs in heat stress will ingest copious amounts of water, increase recreational water use and reduce FI and activity (Kellner et al, 2016;Lucy and Safranski, 2017). At the cellular level, heat stress results in increased expression of chaperone proteins such as HSP70 that help prevent protein misfolding and in the renaturation of misfolded proteins (Brown, 1990;Clerico et al, 2015).…”
Section: Discussionmentioning
confidence: 99%